PRESCHOOL EDUCATION INSTITUTION WORK TARGETED DONE IN INCREASING THE MANAGER ROLE AND PLACE (International Conference on Educational Discoveries and Humanities, 2025)
This in the article preschool education institution young generation perfect human in being in place the manager main tasks place received. Manager this task to perform in the process Both the educator and the students work targeted done in progress actions about briefly description given.